Role of Computed Tomography (CT) in traumatic head injury evaluation – a cross-sectional study - D Venkata Ramanana Rao; Dr. Vinay NVP; Suneetha K S; T. Jaya Chandra (International Journal of Medical Research and Review, 2020)
Introduction: CT is the single primary modality in the evaluation of patients with acute head injuries. With these, a study was taken to find various clinico radiological patterns of head injuries and to correlate the CT features with clinical operative findings.Materials and Methods: This was a cross-sectional study carried in patients of head injury. The patients with a head injury, craniofacial trauma who underwent CT scanning were included in the study. Patients on the ventilator and with Glasgow coma scale <6 were excluded. Patients were scanned using dual Slice CT, Siemens somatom Emotion duo. A P-value of less than 0.05 was considered statistically significant.Results: Total 223 patients were included, 76.2% were males and 73.5% were abnormal scans. Among all intracranial traumatic lesions (ITL) the incidence of multiple ITLs were the most common (35%) and the death rate was 12.6%. Temporal bone fractures (15.2%) were the highest.Conclusion: It was concluded that 21 – 40 years is the typical age group for head injuries, common among male and the incidence of mortality rate is more > 61 years. MICTLs are the most frequent type of hematomas.